PEMIDANAAN MELEBIHI ANCAMAN MAKSIMAL PADA TINDAK PIDANA PENGANIAYAAN YANG MENGAKIBATKAN MATINYA ORANG - Dakhi, Yufran (Jurnal Panah Hukum, 2025)
The crime of abuse is a crime that can cause injuries and pain that can endanger or damage the health of the human body and limbs and even cause death. Meanwhile, abuse that results in the death of a person is an act of crime against a person's body or soul, where in formulating an act of abuse that results in death, it must be seen that the person's death was not intended, meaning that the perpetrator did not intend that the abuse he committed would result in death. To minimize these crimes from occurring, law enforcement is needed in accordance with the provisions of applicable laws and regulations with the aim of providing a deterrent effect to perpetrators of criminal acts. Based on this background, the author is interested in conducting research with the title punishment exceeding the maximum threat for criminal acts of abuse. resulting in the death of people. (study decision number 219/Pid.B/2018/PN Bgl). The type of research used is normative legal research using the statutory regulatory approach, case approach and analytical approach. Data collection was carried out using secondary data obtained through library materials consisting of primary legal materials, secondary legal materials and tertiary legal materials. The data analysis used is descriptive qualitative analysis and conclusions are drawn using a deductive method. Based on the research findings and discussion, it can be concluded that punishment exceeding the maximum threat for criminal acts of abuse which result in the death of a person (decision number 219/Pid.B/2018/PN Bgl) is based on the facts revealed at trial taking into account the juridical basis, and non-juridical, and must consider philosophical foundations. Meanwhile, in imposing a crime that exceeds the maximum threat to the perpetrator, the judge pronounces a decision that is not in accordance with the provisions of the applicable laws and regulations, where in Article 351 paragraph (3) of the Criminal Code, the maximum criminal threat limit has been determined for violations of criminal acts of abuse that result in the death of a person. The author suggests that judges in handing down decisions to perpetrators of criminal acts of abuse which result in the death of people should be based on the provisions on threats in the article which are proven at trial so as to provide a sense of justice for both the victim and the perpetrator.